The Lagrangian and Hamiltonian analysis of some relativistic electrodynamics models and their quantization - Bogolubov (Jr.), N.N.; Prykarpatsky, A.K. (Condensed Matter Physics, 2009)
The work is devoted to the study of the Lagrangian and Hamiltonian properties of some relativistic electrodynamics
models and is a continuation of our previous investigations. Based on the vacuum field theory
approach, the Lagrangian and Hamiltonian reformulation of some classical electrodynamics models is devised.
The Dirac type quantization procedure, based on the canonical Hamiltonian formulation, is developed.
Within the approach proposed in the work a possibility of the combined description both of electrodynamics
and gravity is analyzed. Робота присвячена вивченню лагранжевих та гамiльтонових властивостей деяких релятивiстичних моделей електродинамiки i продовжує нашi попереднi дослiдження. Базуючись на теоретикопольовому пiдходi, розроблено Лагранжеве та Гамiльтонове формулювання деяких класичних моделей електродинамiки. Розвинуто процедуру квантування типу Дiрка, що базується на класичному гамiльтоновому формулюваннi. В рамках запропонованого пiдходу аналiзується можливiсть комбiнованого опису електродинамiки i гравiтацiї.